An exploration of the societal perceptions and cultural attitude towards elderly people in Kinondoni municipal council, Tanzania - Ramadhan Said Naibu; Willy Maliganya (Journal of Management and Science, 2025)
Over the years, ageing has generally been regarded as an important policy issue worldwide because of the large proportion of elderly people. Despite efforts to improve access to healthcare and social services, the elderly in Tanzania still face various challenges. However, the effectiveness of NHIF in promoting social protection among elderly individuals in Tanzania, especially in areas like Kinondoni, remains underexplored. This study explored the societal perceptions and cultural attitude towards elderly people in Kinondoni municipal council. The study population comprised elderly individuals residing in selected wards in Kinondoni Municipal Council for quantitative data. A sample size of 394 elderly people was purposively sampled from Mbezi Juu, Kigogo, and Mbweni Wards in the District. Qualitative data were obtained from different groups such as healthcare providers, NHIF staff, district health officers, and village executive officers. Data collection involved mixed-methods that combined questionnaires, in-depth interviews, document reviews, and focus group discussions to obtain the data. In this study, quantitative data analysis involved descriptive statistics to summarize the results using the Statistical Package for Social Sciences (SPSS). For qualitative data, thematic analysis was employed to identify key themes, patterns, and insights from the qualitative data collected through in-depth interviews. The study revealed that societal perceptions and cultural attitudes significantly influenced the access of elderly people to healthcare, with positive perceptions correlated with age (χ² = 10.35, p = 0.006), gender (χ² = 4.12, p = 0.047), marital status (χ² = 5.89, p = 0.032), and education level (χ² = 9.75, p = 0.008). At the same time, 44% of respondents reported experiencing discrimination, highlighting systemic ageism that impedes adequate care for the elderly. The findings reveal a complex scenery where societal perceptions and cultural attitudes towards the elderly are mixed, with respect coexisting alongside age-related stigma and discrimination. Consequently, the study recommends for targeted awareness campaigns, streamlined NHIF enrolment, financial assistance, culturally sensitive healthcare policies, specialized provider training, and community involvement, robust monitoring systems for improved access and care for elderly individuals under the NHIF.